The relationship between nitrate and phosphate nutrients and phytoplankton abundance in coastal waters: Implications for ecosystem dynamics - Yunus, Muh.; Samawi, Muh. Farid; Jalil, Abd. Rasyid (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: The presence and abundance of phytoplankton are closely related to the physical and chemical parameters of water. Phytoplankton play a crucial role in aquatic ecosystems as primary producers and nutrient absorbers. This study aims to analyze the relationship between nitrate and phosphate nutrient content and the abundance of phytoplankton in the Arungkeke Waters, Jeneponto Regency. Methods: This research utilized a combination of field measurements and laboratory analysis. Direct measurements in the Arungkeke waters were conducted to assess surface water parameters, including temperature, salinity, current velocity, transparency, and ph. Water samples were collected for laboratory analysis of phytoplankton composition and abundance, as well as nitrate and phosphate concentrations. Regression analysis was performed to determine the relationship between nutrient concentrations and phytoplankton abundance. Findings: The study identified two classes of phytoplankton present in the Arungkeke waters: Bacillariophyceae and Dinophyceae. Oceanographic parameters were measured, with temperature ranging from 28.3°C to 29.7°C, current velocity from 0.039 m/s to 0.073 m/s, salinity from 29.3 ppt to 32 ppt, transparency from 1.9 m to 2.3 m, and ph from 7.3 to 7.4. Nitrate concentrations ranged from 0.042 mg/L to 0.076 mg/L, while phosphate concentrations ranged from 0.046 mg/L to 0.056 mg/L. The regression analysis revealed a moderate relationship between phytoplankton abundance and nutrient concentrations, with an R² value of 0.44. Conclusions: The study concludes that phytoplankton abundance in the Arungkeke Waters is influenced by nitrate and phosphate concentrations, with a moderate correlation observed. The presence of Bacillariophyceae and Dinophyceae classes indicates the ecological significance of these waters as a primary production area. Novelty/Originality of this article: This study provides valuable insights into the interaction between nutrient dynamics and phytoplankton abundance in the Arungkeke Waters, which is a relatively understudied area. By identifying the classes of phytoplankton present and quantifying their relationship with key nutrients, this research contributes to a better understanding of the ecological processes in coastal waters.